Causal Evidence for Exclusively Positive Parenting and for Timeout: Rejoinder to Holden, Grogan-Kaylor, Durrant, and Gershoff (2017). Issue 4 (18th May 2020) - Larzelere, Robert E.; Gunnoe, Marjorie L.; Roberts, Mark W.; Lin, Hua; Ferguson, Christopher J.
Abstract: In our initial article we raised concerns about a paradigm we called "Exclusively Positive Parenting" (EPP). This paradigm opposes all negative disciplinary consequences, including timeout and privilege removal. We argued that the empirical support for EPP was insufficient. Researchers should not rely on insufficient causal evidence to replace well-established parenting perspectives that combine positive parenting with appropriate firm control. In reply, Holden et al. defended EPP. In this rejoinder to them we do two things. First, we use their citations to evaluate the limited causal evidence (four randomized studies) for what EPP supports. Second, we summarize the evidence for timeout, which EPP opposes. To do that, we offer the first known meta-analysis of the overall effectiveness of timeout, based on 24 studies with strong causal evidence for its effectiveness with young oppositional defiant children (6 randomized clinical studies; 18 small- N experimental designs). We call for parenting researchers to synthesize positive parenting techniques and disciplinary consequences based on adequate causal evidence.